Thrombin activation of PAR-1 contributes to microvascular stasis in mouse models of sickle cell disease - Sparkenbaugh, Erica M. (Blood, 2020)
Vaso-occlusive crisis (VOC) is the primary cause of morbidity and hospitalization in sickle cell disease (SCD); however, only 4 therapies (hydroxyurea, l-glutamine, crizanlizumab, and voxeletor) are currently approved in SCD. These agents limit the duration, severity, and frequency of crises. Activation of coagulation is a hallmark of SCD. Studies in animal models of SCD have shown that coagulation contributes to the chronic inflammation and end-organ damage associated with the disease; however, it is unknown whether coagulation directly contributes to the microvascular stasis that causes VOC. Herein, we demonstrate that inhibition of tissue factor (TF) and the downstream coagulation proteases factor Xa and thrombin significantly attenuates heme-induced microvascular stasis in mouse models of VOC. Pharmacologic inhibition of the principal thrombin receptor, protease activated receptor-1 (PAR-1), as well as deficiency of PAR-1 in all nonhematopoietic cells, also reduces stasis in sickle mice. PAR-1 deficiency was associated with reduced endothelial von Willebrand factor expression, which has been shown to mediate microvascular stasis. In addition, TF inhibition reduces lung vaso-occlusion in sickle mice mediated by arteriolar neutrophil-platelet microemboli. In sum, these results suggest that prophylactic anticoagulation might attenuate the incidence of VOC.